Development of technical specifications of medical devices in the framework of health technology assessments during the COVID-19 Pandemic: A review of the worldwide scenario and the experience from Peru - Palomares, Ricardo (2022)
Background: Given the health emergency caused by COVID-19, the need for the use of medical devices was particularly relevant. Methodology: A non-systematic literature search was conducted to identify documents that address topics related to the development, implementation, evaluation and/or characteristics of technical datasheets for medical devices. In addition, the SAP System was reviewed for the collection and analysis of data related to pre-pandemic (2000-2019) and in-pandemic (2020-2021) procurement. Evidence: At the global level, the experiences of WHO, ECRI Institute and INAHTA were described. At the Latin American level, experiences were found in Ecuador, Colombia, Argentina, Brazil, Mexico and Panama. Finally, at the Peruvian level, the experience of EsSalud was reported, showing that, from March 6, 2020 to May 21, 2021, 47 technical specifications were prepared for medical devices, of which 41 had purchase records, and of these, 13 correspond to biomedical and complementary equipment. We prioritized the reporting of consumption information (expressed in quantities purchased) for three devices: compact pulse oximeter, high-flow oxygen therapy equipment and the oxygen concentrator (10 L/min). Conclusion: The preparation of technical sheets considers the best scientific evidence available, as well as the technical-technological aspects of the medical device. In EsSalud, its preparation has allowed the incorporation of a significant quantity and variety of biomedical equipment for the treatment of COVID-19, in addition they have been made available with recommendations for their clinical use based on the scientific evidence analyzed.